The Effect Of Product Quality And Price On Consumers Satisfaction - Ryan Feryana Kurniawan; Dewi Ratnasari (Journal of Bussines Management Basic, 2022)
The study aims to determine and analyze the effect of product quality and price on consumer satisfaction (study empirical based on PT. Maulana Mappajaji Sumedang). The methode use is explanatory research and hypothesis testing. By distributing questionnaires to 61 responden. The data analysis technique used is descriptive analysis, validity test, reliability test, classical assumption test, multiple linear regression analysis, coefficient of determination analysis, and hypothesis testing with partial test (t test) simultaneous test (F test). The results of the partial test (t test) show that the product quality variable has a significant and significant effect on consumer satisfaction with a value of 3.358 > 1.671 with a significance level of 0.001 < 0.005. while the price variable has a significant effect on consumer satisfaction with a value of 3.619 > 1.671 with a significance level of 0.001 < 0.005. Then, simultaneously the variables of product quality and price have a significant and significant effect on consumer satisfaction with a value of 8.070 > 3.16 with a significant level of 0.001 < 0.005. Furthermore, based on the results of the coefficient of determination of the product quality variable, a value of 0.177 is obtained, which means that the percentage of the influence of product quality on consumer satisfaction is 17.7%, for the price variable, a value of 0.182 is obtained, which means that the percentage of the influence of price on consumer satisfaction is 18.2%, and for the product quality and price variables obtained a value of 0.218, which means that the percentage of the influence of product quality and price on consumer satisfaction is 21.8%.